Influence of hepatitis C virus replication on splenic lymphoma with villous lymphocytes. - Nunes, Joana (2010)
The association between hepatitis C and B-cell non-Hodgkin lymphoma (NHL) has been suggested by several studies. We report the case of a 70 year-old patient with the diagnosis of chronic hepatitis C and splenic lymphoma with villous lymphocytes, who had undergone splenectomy and chemotherapy with fludarabine, with transient effectiveness. He was sent to our Hepatology Clinic for the treatment of hepatitis C, and Pegylated Interferon and Ribavirin were started. He had virological and hematological response (63% of villous lymphocytes in the peripheral blood at the beginning of therapy and 0% at the end). With the suspension of antiviral therapy, recurrence of HCV infection and reappearance of atypical lymphocytes (24%) were observed, and Pegylated Interferon was restarted, with good response. The relationship between viral and hematologic response (remission and relapse) supports the hypothesis that hepatitis C virus has an active role in the pathogenesis of splenic lymphoma with villous lymphocytes.